Study of Bacterial Meningitis in Children Below 5 Years with Comparative Evaluation of Gram Staining, Culture and Bacterial Antigen Detection - Kala Yadhav ML (Journal of Clinical and Diagnostic Research, 2014)
Context: Bacterial meningitis is one of the most serious infections seen in infants and children, which is associated with acute complications and chronic morbidity. Infections of Central Nervous System (CNS) still dominate the scene of childhood neurological disorders in most of the developing tropical countries. Aims: To isolate, identify and determine the antibiotic susceptibility patterns of pathogens associated with bacterial meningitis. We also aimed to comparatively evaluate of Gram staining, culture and bacterial antigen detection in cerebrospinal fluid samples. Materials and Methods: Present comparative study included 100 CSF samples of children below the age of 5 years, who were clinically suspected meningitis cases. The samples were subjected to Gram staining, culture and Latex agglutination test (LAT). The organisms isolated in the study were characterized and antibiotic susceptibility test was done according to standard guidelines. Statistical Analysis: It was done by using Gaussian test. Results: Of the 100 cases, 24 were diagnosed as Acute bacterial meningitis (ABM) cases by Gram staining, culture and latex agglutination test. 21 (87.5%) cases were culture positive, with 2 cases being positive for polymicrobial isolates. Gram staining was positive in 17 (70.83%) cases and LAT was positive in 8 (33.33%) cases. Streptococcuspneumoniae was the predominant organism which was isolated and it was sensitive to antibiotics. Conclusion: In the present study, male to female ratio was 1.27:1, which showed a male preponderance. With the combination of Gram staining, culture, and LAT, 100% sensitivity and specificity can be achieved (p < 0.001). Gram staining and LAT can detect 85% of cases of ABM. Bacterial meningitis is a medical emergency and making an early diagnosis and providing treatment early are life saving and they reduce chronic morbidity.